Risk Factor and/or Prevalence of Tuberculosis in Nepal: A Systematic Literature Review (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2023)
Objective: The objective  of this review was to synthesise evidence regarding     the  risk factor and/or prevalence  of Tuberculosis in the Nepalese community. Method: A  search strategy was used to identify the English language primary research studies published on or   after 2018. Four  databases namely, Cochrane, PubMed, ProQuest, and  Web of Science were used to search data, and themes were identified  to synthesise the data.Results: A sum of 1097 studies were recognised after the four database searches, excluding duplicates. Just four studies met the inclusion criteria after full article screening and were included for synthesis All the included studies showed evidence on prevalence  of Tuberculosis. Three studies identified male gender as a risk factor for contracting Tuberculosis. Three studies showed the prevalence of Tuberculosis in health disorder context to be around or over 10%, only one study showed about four percent of prevalence of Tuberculosis in admitted patientsConclusions:    Male genders  possess a  greater risk of contracting  Tuberculosis in  health disorder context , with the  exception in Rifampicin-resistant Mycobacterium Tuberculosis(RR-MTB) which showed the opposite outcome. In terms of prevalence ,   majority of the sample exhibited  around ten percent  and over  prevalence  of Tuberculosis in  health disorder context , apart from one study which showed around four percent  prevalence  of Tuberculosis in admitted patients. Therefore, further research is required to bridge these gaps. Moreover,  there is a  gap  in the literature in terms of  study location, population ,  and study design.